+0  
 
+1
279
1
avatar+1442 

If f(x)=g(g(x))-g(x) and g(x)=2x-1, find f(3).

 

Thats my last question for now... Thanks for all the help!

 Nov 30, 2017
 #1
avatar+95883 
+1

Let's first find  g (g(x)) 

 

This is literally putting g(x)  into the x in  g(x)....so we have.... 

 

2 [ 2x - 1]  -  1    =    4x - 3

 

So  

 

g (g(x))  - g (x)   =

 

[ 4x - 3 ] - [ 2x  - 1 ]  =

 

2x  - 2    =  f(x)

 

So

 

f(3)   =  2(3) - 2     =   4

 

 

cool cool cool

 Nov 30, 2017

16 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.